Constructing Informal Learning Method Guidebook for the Music Ensemble Course at Liupanshui Normal University, Guizhou Province, China - Dian , Zhang; Hirunrux, Sakchai (Journal of Roi Kaensarn Academi, 2024)
The objective of this research were (1) To study the informal learning method and the music ensemble course at Liupanshui Normal University of Guizhou (LPSNU), (2) To construct a guidebook on informal learning methods for the music ensemble course at LPSNU, (3) To experimental with the informal learning method guidebook for the music ensemble course at LPSNU, and (4) To study the efficiency of the inform learning methods guidebook for music ensemble at LPSNU. The research methodology is a mixed-methods approach. Qualitative research methods included interviews, conducted with three experts, and an academic study of informal learning methods. The quantitative research method involved testing the teaching effectiveness of the guidebook using statistical test score data. The purposive sample consisted of two ensembles from 3rd-year music major students, with five students in each group, totaling 10 students. Hypothesis: The learning outcomes from formative and summative assessments will not be less than 80/80 percent. The research findings were as follows: (1) Informal Learning Method refers to the process through which individuals accumulate knowledge, skills, and understanding. This typically occurs through self-directed learning, observation, social interactions, and practical experiences. The objectives of the Music Ensemble course are: 1) Technical and Performance Skills 2) Ensemble Techniques 3) Musical Understanding 4) Music Composition and Arrangement 5) Team Collaboration, and 6) Performance Experience (2) the Guidebook consists of: 1) Informal Learning Methods and Principles. 2) Syllabus of the Instrumental Ensemble in LPSNU. 3) Lesson Plans with Informal Learning Settings. 4) Ensemble Guide, and 5) Music Score (7 songs from the band Beyond), and (3) The researchers applied the guidebook to teaching over 16 weeks, once with one 90-minute session per week. Four tests were administered: three formative tests and one summative test, and (4) The average score for the formative tests was 80.93, and for the summative test, it was 86.00—both higher than the hypothesized scores (80 for both formative and summative). This indicates that the informal learning method guidebook for the music ensemble course at LPNU was more effective than anticipated.